2020
DOI: 10.1088/1674-1056/ab928d
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HIV-1 antigen based on magnetic tunnel junction sensors*

Abstract: We report a p24 (HIV disease biomarker) detection assay using an MgO-based magnetic tunnel junction (MTJ) sensor and 20-nm magnetic nanoparticles. The MTJ array sensor with sensing area of 890 × 890 μm2 possessing a sensitivity of 1.39 %/Oe was used to detect p24 antigens. It is demonstrated that the p24 antigens could be detected at a concentration of 0.01 μg/ml. The development of bio-detection systems based on magnetic tunnel junction sensors with high-sensitivity will greatly benefit the early diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…[292][293][294][295][296][297][298] Since interferents and non-specific molecules in complex biological media are nonmagnetic in nature, virus detection with magnetic sensors is significantly more sensitive than optical and electrochemical techniques. 299 Therefore, several promising techniques such as giant magnetoresistance (GMR), 300,301 magnetic particle spectroscopy (MPS), 302,303 magnetic inductance, 260 and magnetic tunneling junction 304,305 are being explored for virus recognition. Streptavidin functionalized magnetic beads (50 nm) consisting of clusters of 8 nmsized a-Fe 2 O 3 and Fe 3 O 4 nanoparticles can be coupled with biotinylated antibodies to develop rapid (response time: 4 min) affordable (6 $ per chip) GMR chips for H1N1 detection in swine nasal swabs down to 250 TCID 50 mL À1 .…”
Section: As Wellmentioning
confidence: 99%
“…[292][293][294][295][296][297][298] Since interferents and non-specific molecules in complex biological media are nonmagnetic in nature, virus detection with magnetic sensors is significantly more sensitive than optical and electrochemical techniques. 299 Therefore, several promising techniques such as giant magnetoresistance (GMR), 300,301 magnetic particle spectroscopy (MPS), 302,303 magnetic inductance, 260 and magnetic tunneling junction 304,305 are being explored for virus recognition. Streptavidin functionalized magnetic beads (50 nm) consisting of clusters of 8 nmsized a-Fe 2 O 3 and Fe 3 O 4 nanoparticles can be coupled with biotinylated antibodies to develop rapid (response time: 4 min) affordable (6 $ per chip) GMR chips for H1N1 detection in swine nasal swabs down to 250 TCID 50 mL À1 .…”
Section: As Wellmentioning
confidence: 99%
“…Very recently, Li et al experimentally demonstrated the detection of HIV-1 antigen p24 by MTJ sensors with an assay time of less than 10 min and a LOD on the order of 0.01 μg/mL. 84 …”
Section: Mr Platformsmentioning
confidence: 99%
“…Very recently, Li et al experimentally demonstrated the detection of HIV-1 antigen p24 by MTJ sensors with an assay time of less than 10 min and a LOD on the order of 0.01 μg/mL. 84 With improved circuitry design and the ease of nanofabrication, there is a trend to use MTJ sensors for bioassays. Gervasoni et al used a 12-channel dual lock-in platform to improve the circuitry for signal generation and acquisition in their MTJ sensing system.…”
Section: Mr Platformsmentioning
confidence: 99%
“…Meanwhile, the MR immunoassay achieved LODs at the level of 10 ng/mL and 50 ng/mL for detection of human immunoglobulins G and M (IgG and IgM) [184]. MR biosensors were also applied in detecting hepatitis B virus (HBV), hepatitis E virus (HEV), and human immunodeficiency virus (HIV) [185][186][187].…”
Section: Mr Sensors In Biomedical Sensing Systemsmentioning
confidence: 99%